MODIFIKASI SLIMS 7 CENDANA SESUAI DENGAN KEBUTUHAN PERPUSTAKAAN PERGURUAN TINGGI - Andi Saputra (Perpustakaan Nasional RI, 2017)
The basic difference between a university library and a public library is on its membership basis; the university library is based on faculty and department, while the public library is based on institution. The Senayan Library Management System (SLiMS) application was originally designed for public libraries. Therefore, the membership database in its membership feature needs to be modified before being implemented in a university library. This study was conducted by modifying SLiMS 7 Cendana application in accordance with the needs of university libraries. Begin with membership base modification on membership feature. After that, experiments were conducted to observe its effect on other modules in application. The modules in SLiMS application are related to each other and supported by a relational database, hence this change had an impact on other modules, such as error messages that come up, incompatibility of column heading and data that not appear as requested. Therefore, to make SLiMS application suitable for the needs of universities, the modification must be done thoroughly, especially modules that relate to the membership module, such as circulation module, membership card, visitor counter and reporting.